The impact of prehabilitation interventions on affective and functional outcomes for young to midlife adult cancer patients: A systematic review. Issue 12 (4th October 2022) - Scriney, Aideen; Russell, Amy; Loughney, Lisa; Gallagher, Pamela; Boran, Lorraine
Abstract: Objective: Cancer remains one of the most enduring health crises of the modern world. Prehabilitation is a relatively new intervention aimed at preparing individuals for the stresses associated with treatment from diagnosis. Prehabilitation can include exercise, psychological and nutrition‐based interventions. The present systematic review aimed to assess the efficacy of prehabilitation on affective and functional outcomes for young to midlife adult cancer patients (18–55 years). Outcomes of interest included prehabilitation programme composition, duration, mode of delivery and measures used to determine impact on affective and functional outcomes. Methods: The following databases were searched with controlled and free text vocabulary; Psychological Information database (PsychINFO), Culmunated Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrieval System Online (MEDLINE), Excerpta Medica Database (EMBASE) and Public MEDLINE (PubMed). Abstract and full‐text screening was conducted with a secondary reviewer and final texts were subject to risk of bias analysis. Results: Thirteen texts were included at full‐text. These included data of 797 prehabilitation participants (mean age 53 years) and a large representation of female participants (71% average). Evidence was found for the efficacy of psychological prehabilitation for anxiety reduction. Prehabilitation did not significantly affect health related quality of life. Findings moderately supported the therapeutic validity of exercise prehabilitation for functional outcomes, both in terms of clinical and experimental improvement with respect to the quality of evidence. Variation between all prehabilitation types was observed. There was insufficient evidence to support the efficacy of psychological prehabilitation on stress, distress or depression. Conclusion: Implications for future research are highlighted and then discussed with respect to this young to midlife age group.